Tip and the Gipper [compact disc, unabridged] : When Politics Worked - Matthews, Chris, 1945- (Audioworks/Simon & Schuster Audio, 2013)
The story of the friendship between President Reagan and the Speaker of the House. They were the political odd couple-the two most powerful men in the country. For six years the author was on the inside, watching the evolving relationship between Ronald Reagan and Tip O'Neill. Their philosophies were miles apart-Reagan intent on scaling back government, O'Neill fervent in defending it. Yet there was common: long lunches shared on St. Patrick's Day and a mutual respect-political and personal.